Adult with Middle Interhemispheric Variant of Holoprosencephaly: Neuropsychological, Clinical, and Radiological Findings. (26th May 2016) - Virta, Maarit; Launes, Jyrki; Valanne, Leena; Hokkanen, Laura
Abstract : Objective: The middle interhemispheric variant of holoprosencephaly (MIHV) is a mild, rare variant of holoprosencephaly. Only a few cases of children with MIHV have been reported. Here we report in detail an adult case. Method: The patient is a female in her 30s. The patient underwent an extensive neuropsychological examination, a neurological examination and a magnetic resonance imaging. Results: Neuroradiologically, the patient had a typical finding of MIHV, with the absence of the central corpus callosum and union of posterior frontal and anterior parietal gyri. In neuropsychological examination, the patient had average or above average performance in verbal comprehension, naming, reading and writing, and below average performance in perceptual reasoning, visuospatial abilities, processing speed and memory. Also difficulties in mathematical abilities, psychomotor skills, and executive functions were found. No gross neurological involvement was noted. She was diagnosed with atypical depression, post-traumatic stress disorder and a dissociative disorder in early adulthood. Despite cognitive deficits, she was able to achieve a tertiary level education. Conclusions: This is the first adult case of MIHV described in detail. Our case emphasizes the possibility of a missed diagnosis of marked brain malformations in patients with craniofacial abnormalities. More cases and prospective follow-up studies are needed to understand the evolvement of both neuropsychological and psychiatric symptoms in these patients.